Application of Flow Cytometry in the Diagnostics Pipeline of Primary Immunodeficiencies Underlying Disseminated Talaromyces marneffei Infection in HIV-Negative Children - Lee, Pamela P.; Lao-araya, Mongkol; Yang, Jing; Chan, Koon-Wing; Ma, Haiyan; Pei, Lim-Cho; Kui, Lin; Mao, Huawei; Yang, Wanling; Zhao, Xiaodong; Trakultivakorn, Muthita; Lau, Yu-Lung (Frontiers in Immunology, 2019)
Talaromyces (Penicillium) marneffei is an AIDS-defining infection in Southeast Asia and is associated with high mortality. It is rare in non-immunosuppressed individuals, especially children. Little is known about host immune response and genetic susceptibility to this endemic fungus. Genetic defects in the interferon-gamma / STAT1 signaling pathway, CD40 / CD40 ligand- and IL12 / IL12-receptor-mediated crosstalk between phagocytes and T-cells, and STAT3-mediated Th17 differentiation have been reported in HIV-negative children with talaromycosis and other endemic mycoses such as histoplasmosis, coccidioidomycosis and paracoccidioidomycosis. There is a need to design a diagnostic algorithm to evaluate such patients. In this article, we review a cohort of paediatric patients with disseminated talaromycosis referred to the Asian Primary Immunodeficiency Network for genetic diagnosis of PID. Using these illustrative cases, we propose a diagnostics pipeline that begins with immunoglobulin pattern (IgG, IgA, IgM, and IgE) and enumeration of lymphocyte subpopulations (T-, B- and NK-cells). The former could provide clues for hyper-IgM syndrome and hyper-IgE syndrome. Flow cytometric evaluation of CD40L expression should be performed for patients suspected to have X-linked hyper-IgM syndrome. Defects in interferon-mediated JAK-STAT signaling are evaluated by STAT1 phosphorylation studies by flow cytometry. STAT1 hyperphosphorylation in response to IFN-alpha or IFN-gamma and delayed dephosphorylation is diagnostic for gain-of-function STAT1 disorder, while absent STAT1 phosphorylation in response to IFN-gamma but normal response to IFN-alpha is suggestive of IFN-gamma receptor deficiency. This simple and rapid diagnostic algorithm will be useful in guiding genetic studies for patients with disseminated talaromycosis requiring immunological investigations.